Improvement of the Elementary School Students’ Reading Comprehension through Generative Learning Model (A Quasi-Experimental Study on Reading Learning Model of the Elementary School Students at Subdistrict South Sumedang, Sumedang Regency) - Asep Saepurokhman (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2016)
This study reports an application of learning model—the so-called generative model considered to be capable of exploring students’ potency, developing their creative thinking, and enhancing their reading comprehension competency. Based on the result of data analysis, it is known that the process of reading-comprehension learning runs well in full activity of students. The students’ tendency to the learning of reading comprehension using such a model is positive in the means of 75.10%. The generative learning model succeeds in enhancing the students’ competence of reading comprehension. The means of score before the treatment is only 53.80%, whereas after the treatment it gets 72% in which the index gain is 0.41 and it is categorized into mediocre. There is difference of reading-comprehension competence between the use of generative learning model and conventional model. It is proven by t-test, indicating that t-observed is higher than t-table. Therefore, the generative learning model is effective and reasonable to use for the teachers in the improvement of stduents’ reading-comprehension competence.